Pengembangan Bahan Ajar Berbasis Informasi Anti-Hoaks dalam Meningkatkan Kompetensi Guru Selama Pandemik Covid-19 - Ramadhani, Rahmi; Ardiyanti, Dwi; Meizar, Abdul (Jurnal Pengabdian Tri Bhakti, 2020)
The Main Potential PKM-University Grant Team conducts Community Partnership Program (PKM) activities in the form of anti-hoax information-based teaching materials development training as part of improving teacher competency. This activity also provides information on how teachers respond to hoax information during the covid-19 pandemic. Participants in this PKM activity are teachers at SMK Namira Tech Nusantara which numbered 24 people. The outside target of Community Partnership Program activities is 1) improving the understanding and knowledge of teachers in making teaching materials by paying attention to the selection of appropriate information and not indicated hoax; 2) improving teachers' skills in designing teaching materials derived from reliable information; and 3) increased motivation of teachers in preparing teaching materials for online-based learning during the covid-19 pandemic. This method of PKM activity is carried out in four stages. The first stage is preliminary observation on the partner school. The second stage is the implementation of teaching materials manufacturing training through the search for hoax information. The third stage is the implementation of anti-hoax-based teaching materials that have been developed. The fourth stage is evaluation and reflection. The result is 1) teachers are able to understand hoax information; 2) teachers are able to develop anti-hoax information-based teaching materials and provide improved teacher competence during the covid-19 pandemic.